2009
DOI: 10.1523/jneurosci.5860-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Convergence of Semantic Processing in Reading and Speech Perception

Abstract: Retrieval of word meaning from the semantic system and its integration with context are often assumed to be shared by spoken and written words. How is modality-independent semantic processing manifested in the brain, spatially and temporally? Time-sensitive neuroimaging allows tracking of neural activation sequences. Use of semantically related versus unrelated word pairs or sentences ending with a semantically highly or less plausible word, in separate studies of the auditory and visual modality, has associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 59 publications
8
52
0
Order By: Relevance
“…Trébuchon et al / Brain & Language xxx (2013) xxx-xxx 7 temporal window (Trébuchon-Da Fonseca et al, 2009). These results are in line with MEG studies in which were compared the patterns of activation evoked by either visually presented or spoken words and were shown that the source of semantic processing, at 400 ms converged along the caudo-rostral axis of the temporal lobe (Marinkovic et al, 2003;Vartiainen, Parviainen, & Salmelin, 2009) especially in the middle part of the STG. Unfortunately, because of the clinical sampling used in these recordings, we have no data recorded in the anterior STG.…”
Section: Discussionsupporting
confidence: 80%
“…Trébuchon et al / Brain & Language xxx (2013) xxx-xxx 7 temporal window (Trébuchon-Da Fonseca et al, 2009). These results are in line with MEG studies in which were compared the patterns of activation evoked by either visually presented or spoken words and were shown that the source of semantic processing, at 400 ms converged along the caudo-rostral axis of the temporal lobe (Marinkovic et al, 2003;Vartiainen, Parviainen, & Salmelin, 2009) especially in the middle part of the STG. Unfortunately, because of the clinical sampling used in these recordings, we have no data recorded in the anterior STG.…”
Section: Discussionsupporting
confidence: 80%
“…For an initial overview of the data, areal mean signals were calculated over 10 regions: occipital, parietal, and the left and right frontal, rolandic, temporal, and occipitotemporal regions (Vartiainen et al, 2009a). The individual areal mean signals were characterized by measuring the mean amplitude in four time windows: 70 -130 ms, 115-150 ms, 130 -250 ms, and 300 -500 ms, that were selected on the basis of the grand-mean and individual signals.…”
Section: Meg Data Acquisition and Analysismentioning
confidence: 99%
“…With the increasing number of studies, apparent differences between MEG and fMRI views of reading have started to form a systematic pattern. Although both methods show involvement of the occipital, occipitotemporal, and temporal cortex in reading, the resulting views of those areas' functional roles are partly inconsistent (e.g., Jobard et al, 2003;Vartiainen et al, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, other MEG studies have identified the middle part of the temporal cortex to be involved in semantic processing [40,41,42]. For example, Vartiainen et al [42] identified the middle superior temporal cortex to be active when presented with lists of semantically similar items, while Helenius et al [40] identified activity in this region in response to sentences with semantically incongruous endings. As with the early N400 literature, these studies do not differentiate responses to familiarity from semantic processing.…”
Section: Discussionmentioning
confidence: 96%
“…A number of other studies have suggested that semantic processing is localised to the superior temporal gyrus [40,41,42]. Recent studies of coherent networks also identified differential semantic and phonological networks during word recognition [18,43].…”
Section: Introductionmentioning
confidence: 99%